2012
DOI: 10.1017/aee.2013.3
|View full text |Cite
|
Sign up to set email alerts
|

Preparing Action Competent Environmental Educators: How Hard Could It Be?

Abstract: This article describes an interpretive study that evaluated a new subject in teacher education called 'Education for Sustainable Development'. The study evaluated the subject for its ability to prepare pre-service teachers for their roles as environmental educators. We used perspectives in place-based pedagogy and critical thinking to underpin the subject design and our analysis. Data sources include instructor journals, planning documents, interviews with students and student thinking books. Interpretive anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
14
0
3

Year Published

2013
2013
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 19 publications
1
14
0
3
Order By: Relevance
“…They felt schools could lead by example to show what could be done about the environment. This observation is in agreement with several studies that have shown how education systems (both schools and higher education) have not fully embraced environmental education, despite the many years of attention to environmental and sustainability issues (Holdsworth et al, 2008;Nielsen et al, 2012). One major reason for this lack of action is that even though schools and universities agree or commit to including environmental and sustainability issues in their curriculum, teachers and academics may not have the necessary support and professional development they need to fully address these issues.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…They felt schools could lead by example to show what could be done about the environment. This observation is in agreement with several studies that have shown how education systems (both schools and higher education) have not fully embraced environmental education, despite the many years of attention to environmental and sustainability issues (Holdsworth et al, 2008;Nielsen et al, 2012). One major reason for this lack of action is that even though schools and universities agree or commit to including environmental and sustainability issues in their curriculum, teachers and academics may not have the necessary support and professional development they need to fully address these issues.…”
Section: Discussionsupporting
confidence: 92%
“…Boubonari et al (2013) describe a similar situation in Greece with regards to concepts related to marine pollution that are superficially touched on in the primary and secondary education. This idea is supported by well-documented research, which shows incomplete implementation of environmental education in schools in different parts of the world (Holdsworth et al, 2008;Nielsen et al, 2012;Spiropoulou et al, 2007).…”
Section: Discussionmentioning
confidence: 85%
“…Por lo tanto, además de tener en cuenta el desarrollo de competencias profesionales específicas relacionadas con la educación ambiental o educación para el desarrollo sostenible (Nielsen et al, 2012;Torquati, Cutler, Gilkerson & Sarver, 2013), es preciso que los educadores incorporen también en la planificación de contenidos y actividades aspectos psicosociales subyacentes a estos temas. Los resultados sugieren que se deben planificar los contenidos en educación ambiental considerando identidad personal y social que encierran la conectividad con la naturaleza y las creencias subyacentes a las preocupaciones ambientales.…”
Section: Discussionunclassified
“…Tal vez el campo de la educación ambiental sea uno de los más prolíficos en cuanto a contenidos y didáctica, pero también es uno en los que persisten lagunas teórico-conceptuales que acompañan la planificación del proceso de enseñanza-aprendizaje (Nielsen et al, 2012). Las políticas de educación ambiental, o de educación para el desarrollo sostenible, suelen carecer de un análisis conceptual profundo y explícito del fin, los medios, la visión de ser humano y la relación que estas ideas guardan con el ambiente, a pesar de que subyacen como supuestos implícitos entre los actores encargados de diseñarlas y ejecutarlas (González-Gaudiano, 2005;Hesselink, van Kempen & Wals, 2000;Navarro, 2011;Olivos & González, 2005).…”
unclassified
“…Anecdotal reports by students indicated that several were keen to participate in further volunteer work in plant nurseries and local council environment groups, indicating that the CUA Day might not be an isolated event in their lives, which bodes well for them as future teachers. It is hoped that these students will incorporate EfS into all areas of classroom practice as they develop their professional identities — for example, using the data from rubbish collection in Maths, to blog their reflections in English, to create photographic collages in Art, and display the corpus of their learning using IT presentation skills (Danielsson & Warwick, 2014; Nielsen et al, 2012). Research by Jones (2013) provides strong support for extending cross-curriculum possibilities, in that being outdoors is a strong stimulus for creativity and group work and ‘liberates’ students from ‘the constraints of the formal classroom and peer judgement’ by taking then ‘away from the safe world of the classroom to extend their limited world of learning’ (p. 107).…”
Section: Discussionmentioning
confidence: 99%